The Clinical Characteristics and Treatment Considerations for Intracranial Aneurysms Associated With Middle Cerebral Artery Anomalies: A Systematic Review - Hou, Kun; Xu, Kan; Liu, Hongping; Li, Guichen; Yu, Jinlu (Frontiers in Neurology, 2020)
Background: As a result of their low incidence, most of the studies on intracranial aneurysms associated with MCA anomalies were presented as case reports or small case series. No systematic review on this specific entity has been conducted. Methods: A PubMed search of the published studies was performed on April 6th, 2019 for patients who had intracranial aneurysms associated with MCA anomalies. The languages included in this study were English, Chinese, and Japanese. Results: Finally, 58 articles reporting of 67 patients including 1 case in our center were included. The identified patients (37 females, 55.2%) aged from 4 to 81 (49.85 ± 15.22) years old. Fifty (50/67, 74.6%) patients presented with hemorrhagic stroke either from the MCA anomalies associated aneurysms or other sources. Sixty-three aneurysms (63/67, 94.0%) were saccular, 3 (4.5%) were dissecting or fusiform, and 1 (1.5%) was pseudoaneurysm. Thirty-two (32/65, 49.2%) patients had other concurrent cerebrovascular anomalies. Fifty-six (83.6%) patients underwent open surgeries, 8 (11.9%) patients underwent endovascular treatment, and 3 (4.5%) patients were conservatively managed. Fifty-six (56/61, 91.8%) patients achieved a good recovery. Conclusions: The pathophysiological genesis of intracranial aneurysms associated with MCA anomalies is still obscure. The inflicted patients tend to have other concurrent cerebrovascular anomalies, which denotes that congenital defect in cerebrovascular development might play a role in this process. Open surgery is, hitherto, the mainstay of treatment. Most of the affected patients could experience a good recovery after treatment.